A multi-strain probiotic formulation preserves intestinal epithelial and vascular barriers during enteropathogenic infection - Naso, Anna Maria; Lizier, Michela; Correale, Carmen; Silvestri, Alessandra; Penna, Giuseppe; Brescia, Paola; Rescigno, Maria (Frontiers in Microbiology, 2025)
BackgroundThe integrity of the intestinal barrier, composed progressively of a mucus, epithelial and vascular layer is critical for maintaining gut homeostasis and preventing systemic translocation of pathogens. Disruptions in any of these protective layers can lead to various health issues, highlighting the need for strategies to preserve barrier function. This study investigated the effects of a multi-strain probiotic formulation (MPF), on intestinal barrier integrity in a murine model infected with Salmonella typhimurium.MethodsC57BL/6 mice were pre-treated with MPF for 10 days before oral infection with Salmonella. Intestinal barrier integrity was assessed through histological analysis, immunofluorescence for key barrier proteins, quantification of bacterial translocation and morphological changes in the ileum and colon.ResultsMice pre-treated with the probiotic formulation exhibited a preserved mucus layer, maintained intestinal epithelial barrier (IEB) integrity, evidenced by sustained expression of mucins and the tight junction protein Zonula occludens-1 (ZO-1), and reduced Salmonella translocation in the colon. Furthermore, the MPF maintained the gut vascular barrier (GVB) integrity by preventing the upregulation of plasmalemma vesicle-associated protein-1 (PV1), typically induced by Salmonella infection. The treatment also mitigated morphological damage, including villus and crypt shortening, caused by the pathogen.ConclusionThese findings suggest that this new formulation of multi-strain probiotics protects against Salmonella-induced damage to both the IEB and GVB, supporting its potential as a therapeutic intervention for managing conditions associated with intestinal barrier dysfunction. Further research is warranted to elucidate the specific mechanisms of action and validate these results in human populations.